Communiti Preaching From a Muhammadiyah: Dakwah Komunitas Perspektif Muhammadiyah - Apris, Apris (Journal Education And Islamic Studies, 2025)
This research aims to explore the concepts, models, strategies, and factors that influence the implementation of community da'wah from the perspective of Muhammadiyah. Community da'wah is seen as a strategic effort to integrate Islamic values into people's lives through a community-based approach. In Muhammadiyah's perspective, community da'wah is based on the principle of Amar Ma'ruf Nahi Munkar and the spirit of Islam Berkemajuan, which prioritises combining religious values with scientific and technological advances. This research uses a descriptive qualitative method with data obtained through a search for previous studies using Google Scholar and Website Dimensions. Further analysis of relevant authors was carried out with the help of VOSViewer software. The research data was sourced from books and relevant online scientific articles. The results showed that the implementation of Muhammadiyah community da'wah uses cultural, structural, and digital technology approaches. Internal factors, such as ideology, human resources, infrastructure, and da'wah methods, provide a strong foundation for the organisation, while external factors, such as social dynamics, economic challenges, technological developments, and relationships with the government and other organisations, become both opportunities and challenges. A planned and adaptive approach makes Muhammadiyah community da'wah able to answer the needs of modern society and make a significant contribution to people's development.